2008
DOI: 10.1128/aem.02688-07
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Shiga Toxin-Producing Escherichia coli Strains Isolated from Hemolytic-Uremic Syndrome Patients and Dairy Samples in France

Abstract: Shiga toxin-producing Escherichia coli (STEC) has been associated with food-borne diseases ranging from uncomplicated diarrhea to hemolytic-uremic syndrome (HUS). While most outbreaks are associated with E. coli O157:H7, about half of the sporadic cases may be due to non-O157:H7 serotypes. To assess the pathogenicity of STEC isolated from dairy foods in France, 40 strains isolated from 1,130 raw-milk and cheese samples were compared with 15 STEC strains isolated from patients suffering from severe disease. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 47 publications
6
52
0
Order By: Relevance
“…This is of particular importance since it has been previously proposed that the Stx2 is the most common virulence factor associated with severe human disease (Pradel et a., 2008). No correlation could be observed between source of isolation (dairy or meat) and the presence of the stx 2 gene.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This is of particular importance since it has been previously proposed that the Stx2 is the most common virulence factor associated with severe human disease (Pradel et a., 2008). No correlation could be observed between source of isolation (dairy or meat) and the presence of the stx 2 gene.…”
Section: Discussionmentioning
confidence: 90%
“…Pradel et al (2008) compared the genotypes of STEC strains isolated from dairy products and from patients. Based on their findings the authors concluded that there was a statistical association between strains isolated from human disease and the presence of the stx 2 gene while the dairy STEC strains were characterized by the predominance of stx 1 , with a limited number of strains carrying the eaeA gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine milk and other dairy products such as yogurt and cheese have been associated with diseases caused by STEC (Chapman et al, 1993;Prandel et al, 2008;Martin & Beutin, 2011). Outbreaks of milk-borne diseases associated with STEC, including pasteurized dairy products, have been reported worldwide emphasizing the importance of STEC control for public health (Morgan et al, 1993;Upton & Coia, 1994;Seghal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of nonclinical sources have shown that STEC serogroup O91 strains are also present in foods. These strains have been isolated from raw milk and cheeses in France (17) and Switzerland (18), from minced beef in France (19), and from cattle feces in Argentina (20), and they are the second most common STEC serogroup found in various types of meats and dairy products in Germany (16). In the United States, STEC O91 strains have been isolated from ground beef (21), from the production environments of other food animals, and also from fresh produce (22).…”
mentioning
confidence: 99%